Trust As a Factor of Crisis Communication During Pandemic Period in SME Companies on The Example of Translation Agency - Marcin JAWORSKI (Communications of International Proceedings, 2021)
The article addresses the problem of communication and the role of trust in the management of an organization from the SME translation sector in times of crisis. The attempt to adapt to the dynamic changes forced on the company in times of crisis may shape the culture of trust and be an opportunity to use this tool in managing the organization, also in the long term. The article contains elements of the theory of trust and the theory of organizational culture, and the influence of communication on shaping the culture in an organization. The author attempted to present a case study of an enterprise from the translation services sector (SME). The research included both factors that to adapt to sudden changes in the workplace and communication with the environment, including the company's team and management. Finally, recommendations and challenges faced by communication managers in an SME organization in a global environment under crisis conditions are presented.
Keywords: Trust; Crisis Communication; Translation Agency